Mapping potential implications of temporary COVID-19 export bans for the food supply in importing countries using precrisis trade flows - Maximilian Koppenberg; Martina Bozzola; Tobias Dalhaus; Stefan Hirsch (Agribusiness, 2020)
Despite pleas from international organizations, governments and trade economists to refrain from imposing trade-distorting measures, over 20 countries have implemented bans on the export of agri-food products since the onset of the COVID-19 crisis. These export prohibitions might adversely impact food security and disrupt well-established global supply chains. We identify importing countries that could potentially be affected by the imposed export bans using a measure of their import dependency during the pre-pandemic period to illustrate our results on global trade maps. We find that many importers rely on just one country for a significant share of the overall domestic supply of a particular commodity. [EconLit Citations: F10, F13, Q17, Q18]
Keywords: 630; agri-food trade; COVID-19; export bans; food security; temporary trade measures